Association of γA/γ’ Fibrinogen Levels and Coronary Artery Disease - Lovely, Rehana S.; Falls, Lisa A.; Al-Mondhiry, Hamid A.; Chambers, Charles E.; Sexton, Gary J.; Ni, Hanyu; Farrell, David H. (Thrombosis and Haemostasis, 2002)
γA/γ’ fibrinogen is a fibrinogen isoform that constitutes about 15% of total plasma fibrinogen. This isoform contains an additional binding site for zymogen factor XIII and for active thrombin, and forms fibrin clots that are resistant to fibrinolysis in vitro. Little is known about the variability of γA/γ’ fibrinogen levels in human populations, whereas total fibrinogen levels are known to increase with age and are higher in women than in men. In this report, evidence is presented that, in contrast to total fibrinogen levels, γA/γ’ fibrinogen levels showed no significant association with age or gender in a population of normal blood donors. A study of γA/γ’ fibrinogen levels in patients undergoing coronary angiography also showed that γA/γ’ fibrinogen levels were higher on average in coronary artery disease patients than in patients without coronary artery disease, and that this association was independent of total fibrinogen levels.
Keywords: Age; coronary; epidemiology; fibrinogen; gender